Peripheral nerve ultrasound: a survival guide for the practicing radiologist with updates - Nouh, Mohamed Ragab; Abdel‑Naby, Hoda Mohamed; El Sakka, Tarek; El-Shafei, Mohamed (The Ultrasound Journal, 2025)
Peripheral nerve injuries negatively impact patients’ quality of life and healthcare resources. This review discusses using high‑resolution neurosonography (HRNUS) for mapping peripheral nerves and detecting pathologic lesions. It emphasizes the importance of HRNUS in diagnosing nerve disorders and briefs the widely accepted schemes for peripheral nerve injury classification. It also highlights the non‑intrusive, flexible, patient‑friendly, and cost‑effective nature of HRNUS, making it a valuable tool in managing nerve disorders. The authors recommend the use of HRNUS to enable precise diagnoses, prevent permanent disabilities, and contribute to the efficient utilization of healthcare resources.